Quality of the institutional system and the COVID-19 pandemic: empirical analysis - Грошев, В.А.; Шебеко, Д.К. (Экономика и банки, 2021)
Government responses to the COVID-19 pandemic have failed to stop the spread and reduce the risk of the disease, even in countries with developed healthcare systems. The pandemic is causing a serious crisis with significant social and economic consequences. The research was carried out under conditions of incompleteness and possible unreliability of the initial information. However, the obtained results make it possible to draw the attention of the scientific community to the aspects of combating the COVID-19pandemic and to expand the ability to confront the challenges posed by current and other possible pandemics. The strength of the relationship was established between the mortality rate due to COVID-19 per 100 thousand population, including the healthy population, (DEATHS / 100K POP.) and Worldwide Governance Indicators (“Voice and Accountability” and "Regulatory Quality"); between the mortality rate due to COVID-19 per 100 thousand population, including the healthy population, ( (DEATHS / 100K POP.) and the indicator Life expectancy at birth, total years (2018); between the indicator “Voice and Accountability” and the indicator Life expectancy at birth, total years; between the indicator "Regulatory Quality" and the indicator Life expectancy at birth. It is concluded that the mortality rate from the COVID-19 pandemic depends on the age structure of the population, which in turn depends on the level of quality of the institutional system.